Dehydroepiandrosterone Effect on Toxoplasma gondii: Molecular Mechanisms Associated to Parasite Death - Saé Muñiz-Hernández; Angélica Luna-Nophal; Carmen T. Gómez-De León; Lenin Domínguez-Ramírez; Olga A. Patrón-Soberano; Karen E. Nava-Castro; Pedro Ostoa-Saloma; Jorge Morales-Montor (Microorganisms, 2021)
Toxoplasmosis is a zoonotic disease caused by the apicomplexa protozoan parasite Toxoplasma gondii. This disease is a health burden, mainly in pregnant women and immunocompromised individuals. Dehydroepiandrosterone (DHEA) has proved to be an important molecule that could drive resistance against a variety of infections, including intracellular parasites such as Plasmodium falciparum and Trypanozoma cruzi, among others. However, to date, the role of DHEA on T. gondii has not been explored. Here, we demonstrated for the first time the toxoplasmicidal effect of DHEA on extracellular tachyzoites. Ultrastructural analysis of treated parasites showed that DHEA alters the cytoskeleton structures, leading to the loss of the organelle structure and organization as well as the loss of the cellular shape. In vitro treatment with DHEA reduces the viability of extracellular tachyzoites and the passive invasion process. Two-dimensional (2D) SDS-PAGE analysis revealed that in the presence of the hormone, a progesterone receptor membrane component (PGRMC) with a cytochrome b5 family heme/steroid binding domain-containing protein was expressed, while the expression of proteins that are essential for motility and virulence was highly reduced. Finally, in vivo DHEA treatment induced a reduction of parasitic load in male, but not in female mice.